A room where the Star-Spangled Banner cannot be heard a novel in three parts - Levy, Ian Hideo 1950- (Japanese studies series, 2011)
"Set against the political and social upheavals of the 1960s, A Room Where the Star-Spangled Banner Cannot Be Heard tells the story of Ben Isaac, a blond-haired, blue-eyed American youth living with his father at the American consulate in Yokohama. Chafing against his father's strict authority and the trappings of an American culture that has grown increasingly remote, Ben flees home to live with And¯o, his Japanese friend. Refusing to speak English with Ben, And¯o shows the young American the way to Shinjuku, the epicenter of Japan's countercultural movement and the closest Ben has ever felt to home."--Jacke